Kontaminasi Escherichia coli pada Air Minum Isi Ulang di Wilayah Ciangsana Menggunakan Uji Most Probable Number (MPN): Escherichia coli Contamination in Drinking Water Refills at Ciangsana Region using Most Probable Number Test - Mohammad Maulana Fajar; Muhammad Rizki Kurniawan; Dian Rachma Wijayanti (Borneo Journal of Medical Laboratory Technology, 2023)
Water is a basic need for humans. Human life cannot be separated from water, especially the need for drinking water. Water needs have been sourced from groundwater, river water, rainwater, mountain water, and treated seawater. Water that humans need includes clean and healthy useable water for cooking, washing, and bathing, as well as water that is fit for consumption for drinking purposes. The main use of water and very vital for life is the use of drinking water. Drinking water from depot companies for drinking water refills is an industrial business that processes raw water into ready-to-drink water by consumers. This study aims to determine the presence of Escherichia coli contamination in drinking water sold by refilled drinking water depots in the Ciangsana region. The results of the microbiological analysis showed two out of ten samples were positive for coliform fecal, Escherichia coli.